Cytokine Response to Exercise and Its Modulation - Katsuhiko Suzuki (MDPI AG, 2018)
Strenuous exercise induces such inflammatory responses as leukocytosis (neutrophilia) and symptoms as delayed-onset muscle soreness and swelling. However, the association between inflammatory mediator cytokines and oxidative stress is not fully delineated. Herein, in addition to basic background information on cytokines, research findings on exertional effects on cytokine release and the underlying mechanisms and triggers are introduced. Then, the associations among cytokine responses, oxidative stress, and tissue damage are described not only in overloaded skeletal muscle, but also in other internal organs. Furthermore, we introduce preventive countermeasures against the exhaustive exercise-induced pathogenesis together with the possibility of antioxidant interventions.